CONCEPTUAL BASES OF IMPLEMENTATION BY THE QUALITY MANAGEMENT SYSTEM OF A PRODUCTION ENTERPRISE (INNOVATIVE ECONOMY, 2020)
Biliavskyi V.M., Vlasenko V.V. CONCEPTUAL BASES OF IMPLEMENTATION BY THE QUALITY MANAGEMENT SYSTEM OF A PRODUCTION ENTERPRISEPurpose. The aim of the article is to substantiation of conceptual bases of introduction of a quality management system as a factor of increasing the competitiveness of industrial production at domestic enterprises.Methodology of research. In the process of research, the methods of theoretical generalization and comparison, analysis and synthesis (for substantiating the essence of quality management of production enterprise, for determining the main components of the implementation by the quality management system and its impact on the investment attractiveness of the enterprise), a graphical method (for visualizing the research results) forecasting (in determining strategic directions for increasing the competitiveness of the enterprise), the logical method (for theoretical generalizations, and the formation of research conclusions).Results of researches. The quality management system is structured, which allows the company’s management to take measures to build an effective organizational and operational process. The main scientific and theoretical bases of perfection of the quality management system are researched, which allows to increase the competitiveness of the enterprise. A plan of measures was developed to improve the quality system of industrial production, characterizing the current state of domestic enterprises.Originality. The model of the process of interaction with the customer of industrial products of the enterprise is designed, which allows management to take measures to build an effective quality management system.Practical value. The obtained results of the research can be considered as one of the examples of the search for research ways, the quality management system of a production enterprise, which will later be used to create objective prerequisites and a methodological basis for further research on the given problems.Key words: quality management system; increase of competitiveness; industrial products; production enterprise.
Keywords: Key words; quality management system; increase of competitiveness; industrial products; production enterprise.